The dilemma of the unsatisfied customer in a market model of public administration - Kelly, Jenet M. (2005)
The relationship between administrative service performance and citizen satisfaction has been assumed, but not demonstrated, in the application of market models to public service delivery. Although the citizen satisfaction literature cautions that the link between objective and subjective measurement of service quality is tenuous at best, public-sector professional organizations define a managerial focus on objective measures of service performance as accountability to citizens for outcomes. What if we are wrong? - Reproduced.
Keywords: Public administration